Plasmon polaritons in photonic metamaterial superlattices : absorption effects (2010)
ABSTRACT: We discuss the propagation of electromagnetic waves in layered structures made up of alternate layers of air and metamaterials. The role played by absorption on the existence of electric and magnetic plasmon polaritons is investigated. Results show that plasmon-polariton modes are robust even in the presence of rather large absorption.